Hybridization of a Flexible Cyclooctatetraene Core and Rigid Aceneimide Wings for Multiluminescent Flapping π Systems. Issue 8 (23rd January 2014) - Yuan, Chunxue; Saito, Shohei; Camacho, Cristopher; Kowalczyk, Tim; Irle, Stephan; Yamaguchi, Shigehiro
Abstract The hybridization of flexible and rigid π‐conjugated frameworks is a potent concept for producing new functional materials. In this article, a series of multifluorescent flapping π systems that combine a flexible cyclooctatetraene (COT) core and rigid aceneimide wings with various π‐conjugation lengths has been designed and synthesized, and their structure/properties relationships have been investigated. Whereas these molecules have a V‐shaped bent conformation in the ground state, the bent structure changes to a planar conformation in the lowest excited singlet (S1) state irrespective of the lengths of the aceneimide wings. However, the fluorescence behavior in solution is distinct between the naphthaleneimide system and the anthraceneimide system. The former has a nonemissive S1 state owing to the significant contribution of the antiaromatic character of the planar COT frontier molecular orbitals, thereby resulting in complete fluorescence quenching in solution. In contrast, the latter anthraceneimide system shows an intense emission, which is ascribed to the planar but distorted S1 state that shows the allowed transition between the π‐molecular orbitals delocalized over the COT core and the acene wings. The other characteristic of these π systems is the significantly redshifted fluorescence in the crystalline state relative to their monomer fluorescence. The relationship between the packing structures and the fluorescence properties was investigated by preparing a series of hybrid π systems with different sizes of substituents on the imide moieties, which revealed the effect of the twofold π‐stacked structure of the V‐shaped molecules on the large bathochromic shift in emission.